2021
DOI: 10.3390/ijerph18179342
|View full text |Cite
|
Sign up to set email alerts
|

What Demographic, Social, and Contextual Factors Influence the Intention to Use COVID-19 Vaccines: A Scoping Review

Abstract: Background: During the COVID-19 crisis, an apparent growth in vaccine hesitancy has been noticed due to different factors and reasons. Therefore, this scoping review was performed to determine the prevalence of intention to use COVID-19 vaccines among adults aged 18–60, and to identify the demographic, social, and contextual factors that influence the intention to use COVID-19 vaccines. Methods: This scoping review was conducted by using the methodological framework for scoping review outlined by Arksey and O’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
162
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(207 citation statements)
references
References 79 publications
(493 reference statements)
19
162
5
2
Order By: Relevance
“…The general perception of the COVID-19 vaccine, attitudes among the population and vaccine acceptance, result from a complex combination of demographic, psychological, behavioral, and social factors. A review of 48 articles about the intention to be vaccinated against COVID-19 conducted among the general population found that a person’s age (advanced), sex (male), education level, race/ethnicity, perception of vaccine safety and effectiveness, influenza vaccination history, and self-protection from COVID-19 were all prominent factors associated with the intention to accept the vaccine [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The general perception of the COVID-19 vaccine, attitudes among the population and vaccine acceptance, result from a complex combination of demographic, psychological, behavioral, and social factors. A review of 48 articles about the intention to be vaccinated against COVID-19 conducted among the general population found that a person’s age (advanced), sex (male), education level, race/ethnicity, perception of vaccine safety and effectiveness, influenza vaccination history, and self-protection from COVID-19 were all prominent factors associated with the intention to accept the vaccine [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Partly being organized with the hidden agenda of disseminating extremist ideas [ 12 ], this development often stems from a mistrust towards established political systems – rooted in minority and socioeconomically disadvantaged communities, and fueled by social media campaigns and fake news [ 10 , [13] , [14] , [15] ]. Countermeasures as involving scientific experts in the ongoing discussion are only sometimes productive [ 14 , 16 ], and even highly educated population groups may be in need of additional information around vaccinations to increase an informed decision making [ 13 ]. For already-stretched healthcare personnel, the violation of the moral principle not to inflict harm upon others through their own actions [ 17 ] is hard to take – for instance, if you can directly see a demonstration outside through the hospital window when you are about to intubate a critically-ill COVID-19 patient [ 11 ].…”
Section: From Shortage To Rejectionmentioning
confidence: 99%
“…So far, laypersons' knowledge about potential clinical courses of COVID-19 probably originates from media coverage. However, those with the highest risk for an unfavourable course are the still unvaccinated, not susceptible for scientific educatory measures [ 14 , 16 ]. But are they then prepared for the possibility of intensive care on the one- and resource shortage on the other hand?…”
Section: Are Potential Future Covid-19 Patients Prepared?mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, socio-demographic variables (e.g. gender, age, race/ethnicity, and educational level), influenza vaccination history, self-protection from COVID-19, risk perception of COVID-19 infection, fear of COVID-19, concerns about the efficacy, side effects and safety of COVID-19 vaccines, and trust in authorities are the most prominent factors associated with COVID-19 vaccination willingness (AlShurman et al, 2021; Joshi et al, 2021; Q Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%